PEMUCATAN MINYAK SAWIT MENTAH MENGGUNAKAN ARANG AKTIF - Muhammad Ali, Wahyuni, Haryono (Jurnal Teknik Kimia, 2012)
Crude Palm Oil, CPO, is a strategic commodity that has economic value, because it is a main raw material to manufacture a variety of food consumer products. CPO is the most produced edible oil in the world. The purpose of this research were to find an alternative adsorbent of bleaching earth, i.e. activated carbon,  and to test the ability of activated carbon as bleaching agent in the bleaching process of CPO.  This research was involving, the activation process of carbon, degumming process of CPO with the addition of phosphoric acid, bleaching process with activated carbon, and analysis to the palm oil produced.  In this study, bleaching process carried out at temperature variations of 90, 100, 110, and 120 oC, and variations of the activated carbon’s concentration at 3, 4, and 5% (by weight) for 30 minutes. Based on this research, the activated carbon has potential as alternative adsorbent for bleaching process of CPO with bleaching power of 93% at the bleaching temperatute of 120 oC and concentration of activated carbon by 5% (by weight). In this bleaching process conditions, after degumming process, the resulted palm oil have the brightness level of 40 mg/L Pt, acid value of 5,66 mg KOH/g, phosphor content of 3,31 ppm, and water content of 0,06% (by weight). Keywords : activated carbon, bleaching, concentration of adsorbent, palm oil, temperature.